TP53 Arg72 as a favorable prognostic factor for Chinese diffuse large B-cell lymphoma patients treated with CHOP - Yalu Liu (BMC Cancer, 2017)
Abstract Background TP53 Arg72Pro (SNP rs1042522) is associated with risk of non-Hodgkin lymphoma (NHL). Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of NHL. However, the relationship between this SNP and prognosis of DLBCL in Asians is unknown. Methods Genotyping of TP53 Arg72Pro was done in 425 Chinese DLBCL patients. Two hundred and eighty-nine patients were treated with R-CHOP, and 136 patients received CHOP or CHOP-like as frontline regimen. Three hundred and ninety-six patients were assessable for the efficacy. Results Patients with Arg/Arg and Arg/Pro at codon 72 of TP53 had a higher complete response rate (61% vs. 44%, P = 0.007) than those with Pro/Pro. In the subgroup treated with CHOP or CHOP-like therapy, patients with Arg/Arg and Arg/Pro showed a higher 5-year overall survival (OS) rate than those with Pro/Pro (68.8% vs. 23.2%, P = 0.001). Multivariate Cox regression analysis revealed TP53 Arg72 as a favorable prognostic factor in this group. However, the combination of rituximab with CHOP significantly increased the 5-year OS rate of patients with Pro/Pro to 63%. Conclusion This study revealed TP53 Arg72 as a favorable prognostic factor for Chinese DLBCL patients treated with CHOP or CHOP-like as frontline therapy.